Sacred and secular : religion and politics worldwide - Norris, Pippa; Inglehart, Ronald (Cambridge : Cambridge University Press, 2011)
'This book develops a theory of secularization and existential security, demonstrating that the publics of virtually all advanced industrial societies have been moving toward more secular orientations during the past fifty years, but also that the world as a whole now has more people with traditional religious views than ever before'--
Includes index and bibliography : p. 331-358.
Keywords: Religion and politics; Secularism